Determining the Effects of the Use of Information Technologies on International Cold Chain Logistics - Ceylan, Tuğçe; Danacı, Tuğçe (İbrahim APAK, 2023)
The use of Information Technologies (IT) in International Cold Chain Logistics (CCL) plays an important role in delivering goods, particularly food and pharmaceutical products, to the consumer without losing their final characteristics. In this study, it is aimed to find out which criteria and how strongly the use of IT is effective in international CCL operations. For this purpose, findings obtained from a comprehensive literature review were divided into main criteria and sub-criteria in accordance with the theoretical background of the study, and the research model of the study was structured. In the methodology part of the study, the Analytical Hierarchy Process (AHP), which is one of the multi-criteria research methods, was used. Questionnaire forms prepared in accordance with the research model and the method were sent to international CCL experts by e-mail, and six of them, which were filled in completely, included in the analysis. Results of the study revealed that IT applications were most effective in Technology-oriented criteria in CCL, and among these criteria, temperature and humidity measurement, and product shelf-life sub-criteria had the highest importance weights, respectively. In addition, it was found that the importance weights of the Resource-oriented and Cost-oriented main criteria were close to each other, but they were significantly lower than the Technology-oriented main criteria. It is considered that the findings obtained from this study can be applied in different samples and regions and will contribute to future studies on this subject.

Uluslararası Soğuk Zincir Lojistiğinde (SZL) Bilgi Teknolojilerinin (BT) kullanımı başta gıda ve ilaç ürünleri olmak üzere eşyanın nihai özelliklerini kaybetmeden tüketiciye ulaştırılmasında önemli bir rol oynamaktadır. Bu çalışmada BT kullanımının uluslararası SZL faaliyetlerinde hangi kriterler üzerinde ve ne kuvvetle etkili olduğunun ortaya çıkarılması amaçlanmıştır. Bu amaç doğrultusunda kapsamlı bir şekilde yapılan literatür taraması sonucunda elde edilen bulgular çalışmanın teorik altyapısına uygun şekilde ana kriterler ve alt kriterlere ayrılmış ve çalışmanın araştırma modeli oluşturulmuştur. Çalışmanın metodoloji bölümünde ise çok kriterli karar verme yöntemlerinden biri olan Analitik Hiyerarşi Süreci (AHS) kullanılmıştır. Araştırma modeli ve yöntemine uygun şekilde hazırlanan anket formları uluslararası SZL konusunda uzman profesyonellere e-posta ile gönderilmiş ve bunlardan eksiksiz doldurulan altı tanesi analize dahil edilmiştir. Çalışmanın sonunda BT uygulamalarının SZL’de en fazla Teknoloji yönlü kriterlerde etkili olduğu, bu kriterler arasında ise sırasıyla sıcaklık ve nem ölçümü ile ürün raf ömrü alt kriterlerinin en yüksek önem ağırlıklarına sahip olduğu ortaya çıkmıştır. Ayrıca Kaynak yönlü ve Maliyet yönlü ana kriterlerinin önem ağırlıklarının birbirine yakın olduğu ancak Teknoloji yönlü ana kriterinin önem ağırlığından belirgin bir şekilde düşük oldukları sonucuna ulaşılmıştır. Bu çalışmadan elde edilen bulguların farklı örneklem ve bölgelerde uygulanabileceği ve ileride bu konuda yapılacak çalışmalara katkı sağlayacağı düşünülmektedir.
Bilgi Teknolojileri Kullanımının Uluslararası Soğuk Zincir Lojistiği Üzerine Etkilerinin Belirlenmesi
-
Keywords: Business Administration; İşletme